Interest Rates and Inflation Revisited - Fama, Eugene F (The Review of Asset Pricing Studies, 2019)
Abstract The continuously compounded (CC) interest rate on a one-month Treasury bill observed at the end of month t–1 is the sum of a CC expected real return and a CC expected inflation rate, Rt–1 = Et–1(rt) + Et–1(It). Two approaches are used to split Rt–1 between its two components. In the first, models for rt produce estimates of Et–1(rt), which are used to infer Et–1(It) as Rt–1 – Et–1(rt). The second approach models It to produce estimates of Et–1(It) and infer Et–1(rt) as Rt–1 – Et–1(It). By design, the estimates of Et–1(rt) and Et–1(It) from both approaches have the properties implied by rational bill prices. Received October 10, 2018; Editorial decision December 31, 2018 By Editor Jeffrey Pontiff